Analysis and design of reset control systems - Guo, Yuqian; Xie, Lihua; Wang, Youyi (The Institution of Engineering and Technology, 2015)
The following topics are dealt with: reset control systems design; reset control systems analysis; reset control systems stability; discrete-time reset conditions and conic jump sets.